2023
DOI: 10.3390/antibiotics12010165
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Molecular Features of Colonizing Isolates of Pseudomonas aeruginosa and the Report of a Novel Sequence Type (ST) 3910 from Thailand

Abstract: Pseudomonas aeruginosa is an important pathogen as it can cause hospital-acquired infections. Additionally, it can also colonize in patients and in other various environments. Hence, this study aimed to investigate the antimicrobial susceptibility, and to study the molecular features, of colonizing isolates of P. aeruginosa from Songklanagarind Hospital, Thailand. Genomic DNA extraction, whole-genome sequencing (WGS), and bioinformatics analysis were performed in all studied isolates. The findings demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…To further explore the potential of phage Callisto for medical and biotechnological applications, we tested the host spectrum, investigated the efficiency of plating (EOP) of the phage against lab strains and clinical strains of Pseudomonas spp. 41 , 42 and examined the presence of unwanted genes in the phage genome associated with bacterial virulence, antibiotic resistance, and the lysogenic life cycle that are disadvantageous for phage therapy. The results revealed that phage Callisto had a relatively broad host range compared to phage PhiKZ, 41 as indicated by its potential to form a clear zone in approximately half of the Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the potential of phage Callisto for medical and biotechnological applications, we tested the host spectrum, investigated the efficiency of plating (EOP) of the phage against lab strains and clinical strains of Pseudomonas spp. 41 , 42 and examined the presence of unwanted genes in the phage genome associated with bacterial virulence, antibiotic resistance, and the lysogenic life cycle that are disadvantageous for phage therapy. The results revealed that phage Callisto had a relatively broad host range compared to phage PhiKZ, 41 as indicated by its potential to form a clear zone in approximately half of the Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…This study is part of a short-term surveillance effort conducted in ICU patients from five different hospitals in Southern Thailand over a 6-month period in 2019 [ 34 , 35 , 36 ]. The project identified 241 Enterobacteriaceae suspected of being resistant to carbapenem antimicrobials, all screened for resistance using MacConkey agar supplemented with 2 µg/mL of imipenem.…”
Section: Methodsmentioning
confidence: 99%